Short-Term Application of Alfalfa Green Manure Increases Maize Yield and Soil Fertility While Altering Microbial Communities in Karst Yellow Clay Soil - Xiaoye Gao; Shimei Yang; Yan He; Qiumei Zhao; Tao Zhang (Microorganisms)
Green manure effectively improves soil nutrients and crop yields, yet its partial substitution for chemical nitrogen fertilizer (CF) in maize systems remains underexplored in ecologically fragile Karst landscapes. To assess the effect of alfalfa green manure on maize yield, soil nutrients, enzymes, and microorganisms, we conducted a two-year field experiment comprising eight treatments: four CF levels (100%, 80%, 60%, and 0% of recommended CF) applied alone or combined with alfalfa green manure (CF100, AL_CF100, CF80, AL_CF80, CF60, AL_CF60, CF0, AL_CF0). The results showed that maize grain yield decreased with the sole reduction of chemical N fertilizer. Compared to the CF100 treatment, the AL_CF100 and AL_CF80 treatments significantly increased grain yield by an average of 21.8% and 16.9%, respectively. Additionally, the AL_CF60 treatment maintained maize grain yield in 2020 and significantly increased it in 2021. The AL_CF100 treatment significantly enhanced soil available N (AN) content, while soil Olsen-P (SOP) content and soil quality index (SQI) were significantly improved in the AL_CF100, AL_CF80, and AL_CF60 treatments. Alfalfa green manure application had no significant effect on soil bacterial and fungal communities. However, the CF rates positively influenced the relative abundances of bacterial phyla (Bacteroidota, Myxococcota, and Patescibacteria) and genera (Intrasporangium, Streptomyces, and Quadrisphaera), as well as fungal genera (Exophiala and Setophoma). α-Diversity analysis revealed that partial substitution of CF with alfalfa green manure did not significantly affect soil bacterial diversity (Ace, Shannon, and Sobs indices) or richness (Chao value). In contrast, chemical N fertilizer rates significantly altered the β-diversity of both bacteria and fungi. The soil AN, AK, sucrase activity, and the relative abundances of Bacteroidota, Streptomyces, and Instrasporangium showed significant positive relationship with maize grain yield. This study demonstrates that substituting 20% CF with alfalfa green manure optimizes maize productivity while enhancing soil health in Karst agroecosystems.